ANALISIS KESULITAN BELAJAR PESERTA DIDIK POLITEKNIK ILMU PELAYARAN MAKASSAR TERHADAP MATA PELAJARAN FISIKA PADA MATERI KECAPATAN DAN PERCEPATAN - Setyaningsih, Agustina; Fauziah, Gradina Nur; Napsawati, Napsawati (Program Studi Pendidikan Fisika FKIP Universitas Muslim Maros, 2024)
Analysis of Learning Difficulties of Students of Politeknik Ilmu Pelayaran Makassar in Physics Subjects on Speed and Acceleration Material. This study aims to identify students learning difficulties in applied physics courses at Politeknik Ilmu Pelayaran Makassar especially on the concept of speed and acceleration. This study is a descriptive study with a population of 240 students in the engineering study program in the first semester of the 2024/2025 academic year and a sample of 150 people based on the Taro Yamane formula. Data collection techniques in this study were written tests and interviews. The research instrument in the form of essay questions was used to measure the difficulty of calculating, mastery of concepts, interpretation of symbols, and unit conversion, and interviews aimed to determine the factors that cause learning difficulties experienced by students. The conclusion of this study shows that the main difficulty of students in learning physics lies in mastery of concepts (20.3%), followed by difficulty in converting units (17.5%) and interpreting symbols (15.9%). The lowest difficulty in calculation (1.1%). Factors such as ineffective teaching methods and lack of supporting materials affect conceptual understanding. Therefore, a more varied learning approach, the use of visual aids, and the improvement of basic mathematical skills are needed to improve students' knowledge of physics.